NURTURING SOCIO-RELIGIOUS HARMONY IN YOGYAKARTA: A STUDY OF PIVOTAL ROLES OF KWT DEWI SRI IN EMPOWERING LOCAL WOMEN - Mahmud Arif; Zulkipli Lessy (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
This research aims to explore local wisdom in a pluralistic society that has been employed by the Female Farmers Group (Kelompok Wanita Tani), also called KWT Dewi Sri, in taking a social role for empowering rural cross-faith women in the hamlet of Kemasan. To implement its vision for local prosperity, KWT Dewi Sri has helped rural women by facilitating socio-empowerment services and informal education for those who are in need. KWT Dewi Sri has given interreligious social services so that the women can build social harmony and thus overcome the cynical assumption that poverty is the fate of being a woman. While embracing the value of benevolent citizenship, KWT Dewi Sri has persuaded these interfaith women to use rational choices to eradicate prejudice against others in general and stigmatisation against women in particular. This research used the qualitative approach with empirical inquiry to explore the females’ accounts of empowering their fellow women and maintaining social harmony in the hamlet. The findings showed that by using adaptive strategies, KWT Dewi Sri demonstrated the benefits of applying preventive programs to counter the take for granted-assumption that being female always necessitates impoverishment. Amid such help and success, many women in the hamlet hold a view, as in Javanese mythology, that KWT Dewi Sri is the reincarnation of the goddess of prosperity (Dewi Sri) descended to empower the local women. This research will discuss the cultural values of KWT Dewi Sri in establishing harmonious lives among people of the hamlet and in empowering the local women, and the obstacles KWT Dewi Sri encounters in embracing its roles.